Clinician perspectives on recovery and borderline personality disorder. Issue 3 (8th May 2017) - Donald, Fiona; Duff, Cameron; Lawrence, Katherine; Broadbear, Jillian; Rao, Sathya
Abstract : Purpose: Recovery is an important concept within mental healthcare policy. There is a growing expectation that clinicians adopt approaches that align with the recovery principles, despite significant disagreements about what recovery-oriented interventions might look like in practice. It is also unclear how recovery may be relevant to personality disorder. This paper aims to discuss these issues. Design/methodology/approach: In total, 16 clinicians were interviewed at two mental health services in Melbourne, Australia. These clinicians had specialist training and experience in the treatment of borderline personality disorder (BPD) and provided insight regarding the meaning and relevance of the recovery paradigm in the context of BPD. Thematic analysis within a grounded theory approach was used to understand key themes identified from the interview data. Findings: Thematic analysis suggested that clinicians understand recovery in three distinct ways: as moving towards a satisfying and meaningful life, as different ways of relating to oneself and as remission of symptoms and improved psychosocial functioning. Clinicians also identified ways in which recovery-related interventions in current use were problematic for individuals diagnosed with BPD. Different approaches that may better support recovery were discussed. This study suggests that practices supporting recovery in BPD may need to be tailored to individuals with BPD, with a focus on cultivating agency while acknowledging the creative nature of recovery. Originality/value: Clinicians are in a strong position to observe recovery. Their insights suggest key refinements that will enhance the ways in which recovery in BPD is conceptualized and can be promoted.